THE LEVEL OF MOTHER'S KNOWLEDGE IN HANDLING FEVER IN CHILDREN IN SUCI VILLAGE, PANTI JEMBER SUB-DISTRICT - Amaliyah Nurul Hidayah; Alfira Septia Wahyuni; Diyan Ajeng Rossetyowati (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2021)
Fever is a condition often found in toddlers. Fever is a condition when the body temperature is above normal temperature (36-37ºC). The general objective of the study was to describe the level of knowledge of mothers in handling fever in children under five years old in Suci village, Panti Jember district. The research used a descriptive design. Samples were taken by random samplingand obtained 81 mothers who have toddlers. This research instrument uses a questionnaire. The results showed that the level of mother's knowledge in handling fever in toddlers in the realm of know was 86%, in the realm of understand was 76%, and in the realm of application was 75%. It can be concluded that the level of mother's knowledge in handling fever in toddlers in Suci village, Panti Jember sub-district in the realm of know and in the realm of understand was a good criterion, and in the realm of application was a fairly good criterion.\Keywords: toddlers, fever, mother's knowledge level